The Importance of Applying Business Ethics in E-Commerce - Putri Mulya Purwaningsih; Trisnawati; Leonita Siwiyanti; Halimah Nursiva (Future Science, 2022)
At this time, the evolution of the use of e-commerce is very clear and many people use e-commerce to buy and sell in technical media. E-Commerce has many advantages, but this system also has many disadvantages. such as fraud because the goods were not sent after the transfer, and the physical goods did not match the picture of the goods listed. For this reason, the role of Islamic business ethics is very important in buying and selling online, because Islam strongly recommends doing justice in business and prohibiting fraud to achieve happiness in the hereafter. Seeing this, we are interested in researching to be able to analyze and find out the application of business ethics in E-Commerce. The research method used is a qualitative method with a literature study. Data collection was carried out by collecting thirteen related articles selected from several journals and websites. The results of this study indicate that e-commerce in the sale of goods and services requires high consumer trust. This high trust needs to be supported by business ethics that must be implemented by all economic executors. E-commerce transactions can be well received by consumers if the business entity applies good business ethics. According to one source cited by the author of Keraf, there are five principles of business ethics: autonomy, honesty, doing good and not doing evil, justice, and respect for oneself. Business people who support the ethical values of Islamic business generally include business people with high integrity.